2015
DOI: 10.1590/1982-43272561201506
|View full text |Cite
|
Sign up to set email alerts
|

Media and Life Dissatisfaction as Predictors of Body Dissatisfaction

Abstract: Body dissatisfaction can contribute to social, occupational and recreational losses, constituting a risk factor to health. This study aimed to evaluate the predictors of body dissatisfaction regarding demographic variables, media and life satisfaction among university students. The sample consisted of 321 participants older than 18 years. Body dissatisfaction, life dissatisfaction and media messages internalization were evaluated by Escala de Silhuetas para Adultos Brasileiros, Subjective Well-Being Scale and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
8
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 19 publications
5
8
0
9
Order By: Relevance
“…The underestimation of BI occurs both in people living in society [19] and those deprived of their freedom, as observed in this and in other studies [12]. The overestimation of body size is also very frequent in women, regardless of their life context [1,4,20]. A Brazilian study with female students revealed a high imprecision in the perception of body size, confirmed by an 81.3% overestimation [20].…”
Section: Discussionsupporting
confidence: 70%
“…The underestimation of BI occurs both in people living in society [19] and those deprived of their freedom, as observed in this and in other studies [12]. The overestimation of body size is also very frequent in women, regardless of their life context [1,4,20]. A Brazilian study with female students revealed a high imprecision in the perception of body size, confirmed by an 81.3% overestimation [20].…”
Section: Discussionsupporting
confidence: 70%
“…A imagem corporal é um construto que abrange diversas esferas e, por esse motivo, são inúmeros os fatores que podem contribuir para a insatisfação, como prática de dietas e os transtornos alimentares 13,16,33,44,55,56,61,78,79,85 , exposição ao conteúdo de mídias e redes sociais 6,12,39,40,88 , sexo feminino 5,6,9,[21][22][23][24][25][26][27][28][29][30][31][32] , além do padrão ocidental de beleza 6,26,48,55,77,78,84,90 .…”
Section: Discussionunclassified
“…Os estudos realizados em SC avaliando esse construto exclusivamente por meio de escalas de silhuetas encontraram elevadas frequências de insatisfação corporal (de 69,5% a 79,2%) para amostra geral 51,57,58,62,68 , enquanto os que utilizaram apenas o BSQ encontraram de 10,1% a 47,7% 11,64 . Também no sul do Brasil (RS e PR) houve frequência de 61,2% e 79,1% para estudos que utilizaram apenas a escala de silhuetas 28,40 Na região sudeste, para estudos que utilizaram apenas escalas de silhuetas, encontraram-se frequências de 75,8% para amostra geral 27 , 82,5% e 73,41% para mulheres e homens, respectivamente 24 ; e a variação foi de 13,7% a 46% 6,38,54 quando apenas o BSQ foi utilizado.…”
Section: Total 421unclassified
See 1 more Smart Citation
“…A médiabeli üzenetek igen erős érzelmi-motivációs hatást gyakorolnak, sokszor tudattalanul hatnak, szubliminális elemeket is beépítve, aminek nem könnyű ellenállni. Ugyanakkor védőfaktorként funkcionálhat az élettel való elégedettség: azok a fiatal nők, akik elégedetlenek az életükkel, hajlamosabbá válnak a kinézettel, a szépséggel, valamint a megjelenéssel kapcsolatos médiabeli üzenetek internalizálására (Jaeger & Câmara, 2015). Ugyanígy az optimizmusról is feltételezhetjük, hogy befolyásolja a médiabeli üzenetekre való fogékonyságot; amint egy vizsgálatból kiderült, kihat a testképpel való elégedettségre (Dalley & Vidal, 2013).…”
Section: A Médiabeli Befolyások Rizikó-és Védőfaktoraiunclassified